Still Resisting Left Melancholy? Chinese New Leftist theatres inheritance and resistance in Che Guevara (Qie Gewala) (20001) - Chen, Chaomei (My University, 2023)
As the fin-de-siècle New Leftist champions of revolution, Zhang Guangtian, Huang Jisu and Shen Lin struck a melancholic note with their collaborative play Che Guevara (Qie Gewala) (2000–1) on the postrevolutionary, depoliticized Chinese stage.1 Why do these Chinese theatre- makers still carry on ‘left melancholy’ amid the worldwide postrevolutionary arena that has bid ‘farewell to revolution’?2 Whose memories and histories do these artists attempt to reclaim and retrieve through this melancholy? How do affective and Marxist theories of ‘left melancholy’ expand the perceptions of recurrent revolutionary pathos in post-revolutionary Chinese leftist theatre? How does the play’s radical recuperation of leftist theatrical techniques, in turn, reinterpret ‘left melancholy’ and resist the marketized, depoliticized trends? This article attempts to depart from and expand the current academic focus on ‘left melancholy’, which has been largely confined to Western leftist theorists such as Walter Benjamin, Wendy Brown and Enzo Traverso, to the postrevolutionary Chinese context. Integrating Western theories with Chinese interpretations of the concept by New Left scholars such as Wang Hui, along with Judith Butler’s theory of subjection (1997), I argue that Che Guevara extends the connotation of left melancholy as a ‘performative paradox’ between an existential, passive despair and a radical, active aesthetic agency of hope to counteract the depoliticized trend of commercial theatre, through an exploration of its affective, theatrical and ideological significance.
PUBLISHED
DOI: 10.1080/13528165.2023.2321059
Keywords: Dramatic/Theatre Arts; Performing Arts; Political theatre; Other; Culture